Safety and efficacy of l‐isoleucine produced by fermentation with Corynebacterium glutamicum KCCM 80189 for all animal species. (18th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of l ‐isoleucine produced by fermentation using Corynebacterium glutamicum KCCM 80189 when used as a nutritional additive in feed and water for drinking for all animal species. The production strain is not genetically modified. Viable cells of the production strain were not detected in the final additive. The additive does not give rise to any safety concern regarding the production strain. l ‐Isoleucine produced using C. glutamicum KCCM 80189 is considered safe for the target species, for the consumer and for the environment. l ‐Isoleucine produced by C. glutamicum KCCM 80189 is considered not toxic by inhalation, not irritant to skin or eyes and not a dermal sensitiser. Regarding the use in water, the FEEDAP Panel reiterates its concerns over the safety of l ‐isoleucine administered simultaneously via water for drinking and feed owing to the risk of nutritional imbalances and hygienic reasons. l ‐Isoleucine produced by C . glutamicum KCCM 80189 is considered as an efficacious source of the essential amino acid l ‐isoleucine for non‐ruminant animal species. For the supplemental l ‐isoleucine to be as efficacious in ruminants as in non‐ruminant species, it would require protection against degradation in the rumen.